Bill Atkin: A Fierce Defender of Children's Rights and Proponent of Child-Focused Legislation - Henaghan, Mark; Ballantyne, Ruth (Victoria University of Wellington Law Review, 2015)
This article illustrates the different ways in which Professor Bill Atkin has shown where family law legislative reforms have fallen short in making the rights and well-being of children the paramount consideration in family law disputes, and properly taking account of children's views on matters that affect them. It examines Atkin's thought-provoking analysis of the introduction of the Care of Children Act 2004 and the changes made in recent years to the Child Support Act 1991, the Property (Relationships) Act 1976 and the Family Court system as a whole. The article also explores Atkin's approval of the amendments to the Crimes Act 1961 preventing parents from using physical discipline against their children for the purposes of correction. Overall, the article highlights Atkin's extensive contribution to family law and demonstrates what needs to be changed to ensure New Zealand family law and society becomes more child-focused in the future.